Comparative advantage and sensitivity analysis of dairy farms by development patterns in West Java - Benny Rachman (Indonesian Center for Animal Research and Development (ICARD), 1998)
The study is aimed at analyzing feasibility of the dairy farm on several development scheme. Domestic resource cost (DRC) analysis is used to understand problems in dairy farms. The study was carried out during August to December 1994 in Bandung and Bogor regencies of West Java . The result of this study indicates that the milk production produced by credit pattern, recommendation pattern and farm group pattern namely, 3,800 liter/ut/year, 4,422 liter/ut/year and 4,270 liter/ut/year, respectively, and also the international market price is Rp. 375/liter tend to be efficient. This phenomena is characterized by coefficient of DRC <1 .0 . Nevertheless, in term of dairy farm development should be based on several aspects such as, economics of scale and scheme of dairy farm. Moreover, farm group pattern (PPK) is more relatively efficient than the others. Keyword : Domestic resource cost (DRC), credit pattern, recommendation pattern, group pattern